Recent advances of the mammalian target of rapamycin signaling in mesenchymal stem cells - Cai, Huarui; Wang, Zhongze; Tang, Wenhan; Ke, Xiaoxue; Zhao, Erhu (Frontiers in Genetics, 2022)
Mammalian target of rapamycin (mTOR) is a serine/threonine kinase involved in a variety of cellular functions, such as cell proliferation, metabolism, autophagy, survival and cytoskeletal organization. Furthermore, mTOR is made up of three multisubunit complexes, mTOR complex 1, mTOR complex 2, and putative mTOR complex 3. In recent years, increasing evidence has suggested that mTOR plays important roles in the differentiation and immune responses of mesenchymal stem cells (MSCs). In addition, mTOR is a vital regulator of pivotal cellular and physiological functions, such as cell metabolism, survival and ageing, where it has emerged as a novel therapeutic target for ageing-related diseases. Therefore, the mTOR signaling may develop a large impact on the treatment of ageing-related diseases with MSCs. In this review, we discuss prospects for future research in this field.